Carbon stock estimation of selected watersheds in Laguna, Philippines using InVEST - Dida, Jan Joseph V.; Tiburan, Cristino L. Jr.; Narumasa Tsutsumida; Izuru Saizen (2021)
"Carbon sequestration is one of the most important forest ecosystem functions that has been recognized globally but the dynamics are highly influenced by the alteration of forest cover. Given the different development thrusts in the Laguna province, the estimation and monitoring of carbon storage become an important activity. This study aims to estimate the carbon stock in the Silang-Santa Rosa and Pagsanjan-Lumban watersheds and explore the possible changes as an effect of land use changes"-title page.
Includes bibliographical references.
Keywords: Land use; Remote sensing; Watersheds -- Research; Watersheds -- Philippines